The image of PISA tests in two colombian newspapers referrals to shape public opinion on the assessment - Torres Zambrano, Guillermo (Avances en Supervisión Educativa, 2014)
The PISA tests applied by OECD in 2012 had a strong impact in Colombia because of the low scores obtained by students . The news had more coverage in the press. In order to establish how they can shape public opinion on the subject because of the manner and direction in which they were addressed, were analyzed news , editorials, opinion columns and letters from readers (total 39 information units) appeared in two Colombian daily newspapers in two and a half months. Recognizing the evaluation as a social fact , the analysis focused around : quality of information sources used , breadth of perspective on the evidence by reference to the evidence and formulate action alternatives . The basic conclusions are : the sources of information to give opinion are very limited, they aren´t criticized and the focus is on the scores ; these show a very negative picture that is extended to all the country’s education ; teachers are largely responsible for the failure. The opinion that the media contribute to form is negative.